Demanded interdisciplinary subjects for integration in medical education program from the point of view of graduated medical physicians and senior medical students: a nationwide mixed qualitative-quantitative study from Iran - Kamran Bagheri Lankarani; Behnam Honarvar; Seyed Aliakbar Faghihi; Mohammad Reza Rahmanian Haghighi; Ahmad Kalateh Sadati; Fatemeh Rafiei; Sayyed Amirreza Hosseini; Amir-Hassan Bordbari; Arash Ziaee; Mohammad Jafar Pooriesa (BMC Medical Education, 2024)
Abstract Introduction This study aimed to detect interdisciplinary subjects for integration into the medical education program of Iran. Methods A qualitative-quantitative method was used. Firstly, interdisciplinary subjects demanded by medical graduates and senior medical students were defined by qualitative study. In the second stage, questionnaire was developed which based on the findings of qualitative stage, experts’ opinion and reviewing of the national general guide of professional ethics for medical practitioners. Questionnaire consisted of demographic, occupational and thirteen interdisciplinary items. These items consisted of social determinants of health, social and economic consequences of disease, social prescribing, physicians’ social responsibility, role of gender, racial, ethnic, social and economic issues in approach to patients, role of logic and mathematics in clinical decision-making, philosophy of medicine, maintaining work-life balance, self-anger management, national laws of medicine, religious law in medical practice, health system structure, and teamwork principles. Level and importance of knowledge and self-assessed educational needs were asked about each item. In the third stage, a national online survey was conducted. SPSS 25 was used for statistics. Results By content analysis of data in qualitative stage, 36 sub-themes and 7 themes were extracted. In the quantitative part, 3580 subjects from 41 medical universities across Iran participated in this study. 2896 (80.9%) were medical graduates and 684 (19.1%) were senior medical students. Overall, knowledge about interdisciplinary items was low to intermediate, while high to very high knowledge ranged from maximally 38.7% about socioeconomic consequences of disease to minimally 17.2% about social prescribing. Participants gave the most importance to the having knowledge about self-anger management (88.3%), maintaining work-life balance (87.2%) and social determinants of health (85.8%), respectively. However, national laws of medicine (77.6%), maintaining work-life balance (75.4%) and self-anger management (74%) were the first top three educational demands by participants. Conclusion This study revealed a low to moderate level of knowledge about interdisciplinary topics among both graduated medical physicians and senior medical students. These groups showed a strong demand and tendency to know and to be educated about these topics. These findings underscore the urgency for educational reforms to meet the interdisciplinary needs of medical professionals in Iran.